Impacts of Translocation on Nigerian International Students’ Eating Habits in North Cyprus (Comparative & International Education Series, 2022)
Generally, translocation is never without complaints/crises, especially when moving from one country to another. International students are a lucrative segment of global tourism. However, the ripple effect of translocation affects their eating habits. Despite the abundance of studies on translocation in animal and plant sciences, literature on the impacts of translocation on international students’ eating habits is scarce. This study explores the impacts of translocation on Nigerian international students’ eating habits in North Cyprus. This qualitative case study used semi-structured interviews to collect data from 13 students at Eastern Mediterranean University, North Cyprus. Findings reveal three themes characterizing their experiences: motivational, economic, and physiological factors. Voyat analysis shows that the major factors affecting their eating habits are; eating, food choice, new environment, and time differences. This study contributes to education and tourism literature. Implications, limitations, and future research are discussed.